Best Teaching and Learning Approaches through the Eyes of Thai EFL Preservice Teachers - Pasara Namsaeng; Wadinlada Thuratham (Journal of Educational Issues, 2024)
The best teaching and learning approaches have been controversial since the origins of language teaching and learning. This study aims to explore the Thai EFL preservice teachers’ perceptions towards the best teaching and learning approaches through the written test. A qualitative research design and purposive sampling were employed to collect data from 46 participants who completed teacher training for at least one semester. Research ethics were obtained prior to data collection. The research instrument was a 150-word written test from 46 participants. The results show that there were 17 features of the best teaching and learning desired by Thai EFL preservice teachers, which can be put into four aspects: lesson, classroom environment, teachers, and students. In detail, lessons should be learned in a group setting using meaningful, real-life situations, simplified language, communication practice, language practice, and thinking practices. The classroom environment should be active, fun, and enjoyable, allowing for freely expressing ideas and opinions and peer-supported learning. Teachers should scaffold, increase motivation, and provide mental support to students. Finally, students must be able to manage their own emotions, have a sense of control over their own learning, and become autonomous learners. The mentioned features are likely to comply with Communicative Language Teaching (CLT). The reasons that the participants weighed in on this approach can probably be due to ready-to-use materials to be used in different communicative situations, exciting and motivating approaches with active activities, and technology-supported language learning, leading to idealized pedagogical implementation.